2017
DOI: 10.1002/anie.201709455
|View full text |Cite
|
Sign up to set email alerts
|

Co‐adsorption of Cations as the Cause of the Apparent pH Dependence of Hydrogen Adsorption on a Stepped Platinum Single‐Crystal Electrode

Abstract: The successful deployment of advanced energy-conversion systems depends critically on our understanding of the fundamental interactions of the key adsorbed intermediates (hydrogen *H and hydroxyl *OH) at electrified metal-aqueous electrolyte interfaces. Herein, the effect of alkali metal cations (Li+, Na+, K+ and Cs+) on the non-Nernstian pH shift of the step-related voltammetric peak of the Pt(553) electrode is investigated over a wide pH window (1 to 13) by means of experimental and computational methods. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
246
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(272 citation statements)
references
References 19 publications
22
246
3
1
Order By: Relevance
“…[20] Therefore,from athermodynamic standpoint on H upd adsorption energy,itisdifficult to explain the significant pH dependence of the HER overpotential on Pt(111) surfaces.A tt he same time,K oper et al argued that the H upd peaks on polycrystalline and stepped single-crystal Pt electrodes is unlikely to be associated with the adsorption of hydrogen alone,a nd that the effect of oxygenated species adsorption needs to be included as well. [20,21] This is consistent with studies by Marković et al,which proposed that adsorbed hydroxyl (OH*) may affect the kinetics of the HER/HOR by competing for the same surface sites with reactive intermediates (blocking effect) and/or altering its adsorption energy (energetic effect). [16b] Moreover,Marković et al reported that the isosteric heat of adsorption for OH* is also independent of pH on Pt(111) surfaces.…”
Section: Debates On Activity Descriptorssupporting
confidence: 88%
“…[20] Therefore,from athermodynamic standpoint on H upd adsorption energy,itisdifficult to explain the significant pH dependence of the HER overpotential on Pt(111) surfaces.A tt he same time,K oper et al argued that the H upd peaks on polycrystalline and stepped single-crystal Pt electrodes is unlikely to be associated with the adsorption of hydrogen alone,a nd that the effect of oxygenated species adsorption needs to be included as well. [20,21] This is consistent with studies by Marković et al,which proposed that adsorbed hydroxyl (OH*) may affect the kinetics of the HER/HOR by competing for the same surface sites with reactive intermediates (blocking effect) and/or altering its adsorption energy (energetic effect). [16b] Moreover,Marković et al reported that the isosteric heat of adsorption for OH* is also independent of pH on Pt(111) surfaces.…”
Section: Debates On Activity Descriptorssupporting
confidence: 88%
“…Theresults displayed in Figure 3would imply that bigger cations (in this case Cs + )provide abetter stabilization to the Ni À OO À À M + intermediate.T his species acts as the precursor to O 2 evolution, explaining the higher activity.T he exact nature of this cation stabilization should be the subject of further computational study (see,e .g., Refs. [34,43]). The model expressed in Equation (2) is subtly different form the model recently put forward by Grimaud et al, [28] who studied the influence of large organic tetra-alkyl ammonium cations,o nt he OER activity of NiOOH and Ni(Fe)OOH catalysts.T hey suggested that the strong interaction with organic cations actually blocks the active site and lowers the OER activity,s pecifically of the Ni(Fe)OOH catalyst.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Our results lend further credit to our mechanism for OER on NiOOH, and provide another example of how electrolyte cations influence the activity and selectivity of electrocatalytic reactions by their specific interaction with active surface intermediates. [31][32][33][34] NiOOH electrocatalysts were prepared by electrochemically assisted precipitation of Ni(OH) 2 on polycrystalline gold. [35] Formeasurements on iron-free catalysts,the electrolytes were purified from Fe using the method described by Boettcher et al [13] See the Supporting Information for further experimental details.…”
mentioning
confidence: 99%
“…Our results confirm the existence of the influence of the alkali metal cations; and this influence strongly correlates with the type of the alkali metal. This influence might indicate the presence of non‐covalent interactions, between alkali metal cations and the adsorbed reaction intermediates at the electrode surface, or it could be due to co‐adsorption of metal cations onto the electrode surface . However, more detailed experiments are needed to fully confirm the exact origin of this phenomenon.…”
Section: Figurementioning
confidence: 99%